Manajemen Pondok Pesantren di Indonesia: Studi Literatur Pendidikan Islam - Achmad Dzulfikar; Abdul Kholiq; Muhammad Muhtadi (Lembaga Yasin AlSys, 2026)
Although pondok pesantren play a strategic role in the Islamic education system in Indonesia, studies that comprehensively examine pesantren management from an educational management perspective remain relatively limited. This study aimed to analyze the management of pondok pesantren in Indonesia with a focus on leadership management, curriculum and instructional management, human resource management, and facilities, infrastructure, and financial management. A qualitative approach with a literature study method was employed. Data were collected through documentation of relevant scientific journal articles, academic books, and research reports published over the last ten years, then analyzed using thematic analysis to identify patterns and main themes related to pesantren management practices. The findings show that pesantren management in Indonesia is still strongly influenced by the central role of the kiai as the main leader with moral and spiritual legitimacy. In terms of curriculum, pesantren demonstrate adaptive capacity through the integration of pesantren and national curricula, although they continue to face challenges in maintaining a balance between deepening Islamic scholarship and developing modern competencies. Human resource management tends to be based on devotion and loyalty, while financial management generally relies on self-funding through student fees, community donations, and pesantren business units. This study provides a theoretical contribution to the development of Islamic education management studies by emphasizing the importance of value-based contextual management approaches, as well as a practical contribution as a reference for pesantren administrators and policymakers in strengthening sustainable pesantren governance.